The Mediating Effect of Emotional Intelligence on the Relationship between Personality Traits and Work Engagement of Library Personnel - Bayot, Rosecil; Bastida, Garry (Journal of Interdisciplinary Perspectives, 2025)
Limited research has examined emotional intelligence as a mediator between personality traits and work engagement, particularly among library personnel. Despite its essential role in shaping work experiences, engagement in the library workplace has received little attention, and the personality traits of library personnel remain understudied. Addressing this gap, the study examined the degree of personality traits, the level of work engagement, and the emotional intelligence of library personnel. It also explored the relationships between these factors and whether emotional intelligence significantly linked personality traits to work engagement. The study used a non-experimental, quantitative design with a descriptive- correlational approach and mediation analysis. Data were collected through adapted questionnaires measuring personality traits, emotional intelligence, and work engagement. A total of 311 library personnel were selected through convenience sampling. Statistical tests, including correlation and mediation analyses, were conducted to determine the relationships between the variables. Findings indicated that library personnel demonstrated strong personality traits, high emotional intelligence, and high levels of work engagement. Personality traits and emotional intelligence were both significantly linked to work engagement. The other thing was the mediation of emotional intelligence on the relationship between personality traits and work engagement-indirect effect exceeding the direct effect. This highlights the importance of emotional intelligence for enhancing job performance, improving professional relationships, and heightening engagement in library work. Enhancement of emotional intelligence can enable library personnel to deal effectively with different challenges encountered in their workplaces and to adapt quickly to varying work tasks to provide enhanced quality service. Emotional intelligence training should be incorporated into leadership programs and recruitment strategies, alongside working seminars, coaching, and mentoring, to increase work engagement and productivity and enhance effective service delivery.